What Do We Know When We Know a Person Across Contexts? Examining Self‐Concept Differentiation at the Three Levels of Personality. Issue 4 (21st February 2013) - Dunlop, William L.; Walker, Lawrence J.; Wiens, Thomas K.
Abstract Objective Previous research examining self‐concept differentiation (SCD) has been characterized by (a) a focus on behavioral traits and (b) the conflation of mean‐level and inter‐contextual differentiation. In two studies, we considered non‐conflated measures of SCD at the three levels of personality description in relation to adjustment. Method In Study 1, participants completed measures of adjustment, rated their behavioral tendencies (dispositional traits), produced a list of goals (characteristic adaptations), and recalled a self‐defining memory (life narratives), from within professional and personal domains. In Study 2, the procedure was modified: Participants reporting either low or high levels of adjustment subsequently rated their behavioral traits, provided a list of goals, or produced a self‐defining memory, from five contexts. Results In Study 1, adjustment related positively to SCD at the level of characteristic adaptations but negatively to SCD at the level of life narratives. In Study 2, well‐adjusted participants exhibited a greater degree of SCD at the level of characteristic adaptations but a greater degree of thematic consistency at the level of life narratives, relative to those low in adjustment. Conclusions These results highlight the dynamic nature of SCD across levels of personality and align with the notion that differentiation represents virtue and vice.